Development of hybrid semi-analytical and finite element analysis to calculate sound radiation from vibrating structure - Putra, Azma; Shyafina, Nurain; Muhammad, Noryani; Bakri, Hairul; Saari, Noor Fariza (Trans Tech Publications, 2014)
Simple analytical model of plate dynamics usually applies for rectangular plate with simply supported edges. Analytical model of sound radiation from rectangular plate is also convenient, but not for other geometries and other boundary conditions. This paper presents a hybrid mathematical model which combines a semi-analytical model with the Finite Element Analysis (FEA) method to determine sound radiation from a vibrating structure. The latter is employed to calculate the vibration velocity of a structure with a rather complex geometry. The results are then used as the input in the semi-analytical model to calculate the radiated sound pressure through the Rayleigh integral. Results from the proposed model are presented here for the radiation efficiency of rectangular plates with different boundary conditions.